Conservative islam : a cultural anthropology - Kolig, Erich (Lexington Books, 2012)
Conservative Islam: A Cultural Anthropology by Erich Kolig analyzes the salient characteristics of Islam and contemporary Muslim society from the perspective of traditional cultural anthropology. By highlighting socio-cultural configurations, the universals they represent, the circumstances of their creation, and their semiotic meaning, Kolig helps the reader gain understanding of Islam in the modern world.